Integrated Approach to Human Rights in a Post Conflict Niger Delta (In Factis Pax: Journal of Peace Education and Social Justice, 2017)
It is the responsibility of Government to provide social guarantees protect the rights of all citizens; the weak and vulnerable in the Niger Delta should not be victims of social forces, which they have no control over. Shue summarized this argument with the Transitivity Principle; he stated: “if everyone has a right to y, and the enjoyment of x is necessary for the enjoyment of y, then everyone has also had a right to x” (p.32). The implication and adaptation of this argument to the Niger Delta situation should be that the people of the Niger Delta has a right and desire political rights, but the enjoyment of the political rights depends on the availability of subsistence. It then follows from the transitivity principle that everybody to enjoy political rights need to have economic rights as well as a right to environmental sustainability.  Therefore, as a matter of human rights and social justice the fundamental rights should be urgently addressed in the Niger Delta. The journey of transformation in the post-conflict Niger Delta should be in the integration of the CP and ESC rights. Priority should be given to ESC rights. There is a need for a proactive engagement, speaking out against violation is not enough, there has to be a concerted effort at empowerment to achieve and sustain an integrated structure of human rights in the Niger Delta.
Keywords: Nigeria; Niger Delta; Justice; Human Rights; Peace Education